Paralegal Students’ and Paralegal Instructors’ Perceptions of Synchronous and Asynchronous Online Paralegal Course Effectiveness: A Comparative Study - Farmer, Kristine; Allen, Jeff; Khader, Malak; Zimmerman, Tara; Johnstone, Peter (International Journal for Educational and Vocational Studies, 2021)
To improve online learning pedagogy within the field of paralegal education, this study investigated how paralegal students and paralegal instructors perceived the effectiveness of synchronous and asynchronous online paralegal courses.  This study intended to inform paralegal instructors and course developers how to better design, deliver, and evaluate effective online course instruction in the field of paralegal studies.Survey results were analyzed using independent samples t-test and correlational analysis, and indicated that overall, paralegal students and paralegal instructors positively perceived synchronous and asynchronous online paralegal courses.  Paralegal instructors reported statistically significant higher perceptions than paralegal students: (1) of instructional design and course content in synchronous online paralegal courses; and (2) of technical assistance, communication, and course content in asynchronous online paralegal courses.  Instructors also reported higher perceptions of the effectiveness of universal design, online instructional design, and course content in synchronous online paralegal courses than in asynchronous online paralegal courses.  Paralegal students reported higher perceptions of asynchronous online paralegal course effectiveness regarding universal design than paralegal instructors.  No statistically significant differences existed between paralegal students’ perceptions of the effectiveness of synchronous and asynchronous online paralegal courses. A strong, negative relationship existed between paralegal students’ age and their perceptions of effective synchronous paralegal courses, which were statistically and practically significant.  Lastly, this study provided practical applicability and opportunities for future research. Akyol, Z., & Garrison, D. R. (2008). The development of a community of inquiry over time in an online course: Understanding the progression and integration of social, cognitive and teaching presence. Journal of Asynchronous Learning Networks, 12, 3-22.  Retrieved from https://files.eric.ed.gov/fulltext/EJ837483.pdf Akyol, Z., Garrison, D. R., & Ozden, M. Y. (2009). Online and blended communities of inquiry: Exploring the developmental and perceptional differences. The International Review of Research in Open and Distributed Learning, 10(6), 65-83.  Retrieved from http://www.irrodl.org/index.php/irrodl/article/view/765/1436 Allen, I. E., & Seaman, J. (2014). Grade change: Tracking online education in the United States. Babson Park, MA:  Babson Survey Research Group and Quahog Research Group, LLC.  Retrieved from https://www.utc.edu/learn/pdfs/online/sloanc-report-2014.pdf Alreck, P. L., & Settle, R. B. (2004). The Survey Research Handbook (3rd ed.) New York, NY: McGraw-Hill Irwin. American Association for Paralegal Education (2013, Oct.).  AAfPE core competencies for paralegal programs.  Retrieved from https://cdn.ymaws.com/www.aafpe.org/resource/resmgr/Docs/AAfPECoreCompetencies.pdf American Bar Association, Standing Committee on Paralegals.  (2017). https://www.americanbar.org/groups/paralegals.html American Bar Association, Standing Committee on Paralegals (2013, September).  Guidelines for the approval of paralegal education programs.  Retrieved from https://www.americanbar.org/content/dam/aba/administrative/paralegals/ls_prlgs_2013_paralegal_guidelines.authcheckdam.pdf Astani, M., Ready, K. J., & Duplaga, E. A. (2010). Online course experience matters: Investigating students’ perceptions of online learning. Issues in Information Systems, 11(2), 14-21.  Retrieved from http://iacis.org/iis/2010/14-21_LV2010_1526.pdf Bailey, C. J., & Card, K. A. (2009). Effective pedagogical practices for online teaching: Perception of experienced instructors. The Internet and Higher Education, 12, 152-155. doi: 10.1016/j.iheduc.2009.08.002 Bernard, R., Abrami, P., Borokhovski, E., Wade, C., Tamim , R., Surkes, M., & Bethel, E. (2009).  A meta-analysis of three types of interaction treatments in distance education.  Review of Educational Research, 79, 1243-1289.  doi: 10.3102/0034654309333844 Cherry, S. J., & Flora, B. H. (2017). Radiography faculty engaged in online education: Perceptions of effectiveness, satisfaction, and technological self-efficacy. Radiologic Technology, 88(3), 249-262.  http://www.radiologictechnology.org/ Cohen, J. (1988). Statistical power analysis for the behavioral sciences (2nd ed.). New York: Taylor & Francis Group. Colorado, J. T., & Eberle, J. (2010). Student demographics and success in online learning environments.  Emporia State Research Studies, 46(1), 4-10.  Retrieved from https://esirc.emporia.edu/bitstream/handle/123456789/380/205.2.pdf?sequence=1 Dutcher, C. W., Epps, K. K., & Cleaveland, M. C. (2015). Comparing business law in online and face to face formats: A difference in student learning perception. Academy of Educational Leadership Journal, 19, 123-134.  http://www.abacademies.org/journals/academy-of-educational-leadership-journal-home.html Faul, F., Erdfelder, E., Lang, A.-G., & Buchner, A. (2007). G*Power 3: A flexible statistical power analysis program for the social, behavioral, and biomedical sciences. Behavior Research Methods, 39, 175-191.  Retrieved from http://www.gpower.hhu.de/fileadmin/redaktion/Fakultaeten/Mathematisch-Naturwissenschaftliche_Fakultaet/Psychologie/AAP/gpower/GPower3-BRM-Paper.pdf Field, A. (2009).  Discovery statistics using SPSS. (3rd ed.).  Thousand Oaks, CA:  Sage Publications, Inc. Gall M., Borg, W., & Gall, J. (1996). Educational research: An introduction (6th ed.). White Plains, NY: Longman Press. Garrison, D. R., Anderson, T., & Archer, W. (2001). Critical thinking, cognitive presence, and computer conferencing in distance education. American Journal of distance education, 15(1), 7-23.  Retrieved from http://cde.athabascau.ca/coi_site/documents/Garrison_Anderson_Archer_CogPres_Final.pdf Green, S. B., & Salkind, N. J. (2005). Using SPSS for Windows and Macintosh: Internal consistency estimates of reliability. Upper Saddle River, NJ: Pearson Prentice Hall. Harrell, I. L. (2008). Increasing the Success of Online Students. Inquiry, 13(1), 36-44.  Retrieved from http://files.eric.ed.gov/fulltext/EJ833911.pdf Horspool, A., & Lange, C. (2012). Applying the scholarship of teaching and learning: student perceptions, behaviours and success online and face-to-face. Assessment & Evaluation in Higher Education, 37, 73-88.  doi: 10.1080/02602938.2010.496532 Inman, E., Kerwin, M., & Mayes, L. (1999). Instructor and student attitudes toward distance learning. Community College Journal of Research & Practice, 23, 581-591.  doi:10.1080/106689299264594 Institute of Legal Executives (ILEX).  https://www.cilexcareers.org.uk/ Johnson, J. & Taggart, G. (1996).  Computer assisted instruction in paralegal education: Does it help? Journal of Paralegal Education and Practice, 12, 1-21. Johnstone, Q. & Flood, J. (1982).  Paralegals in English and American law offices.  Windsor YB Access to Justice 2, 152. Jones, S. J. (2012). Reading between the lines of online course evaluations: Identifiable actions that improve student perceptions of teaching effectiveness and course value. Journal of Asynchronous Learning Networks, 16(1), 49-58.  doi:http://dx.doi.org/10.24059/olj.v16i1.227 Krejcie, R. V., & Morgan, D. W. (1970). Determining sample size for research activities. Educational and psychological measurement, 30, 607-610.  http://journals.sagepub.com/home/epm Liu, S., Gomez, J., Khan, B., & Yen, C. J. (2007). Toward a learner-oriented community college online course dropout framework. International Journal on ELearning, 6(4), 519-542.  https://www.learntechlib.org/j/IJEL/ Lloyd, S. A., Byrne, M. M., & McCoy, T. S. (2012). Faculty-perceived barriers of online education. Journal of online learning and teaching, 8(1), 1-12.  Retrieved from http://jolt.merlot.org/vol8no1/lloyd_0312.pdf Lockee, B., Burton, J., & Potter, K. (2010, March). Organizational perspectives on quality in distance learning. In D. Gibson & B. Dodge (Eds.), Proceedings of SITE 2010—Society for Information Technology & Teacher Education International Conference (pp. 659-664). San Diego, CA:  Association for the Advancement of Computing in Education (AACE).  https://www.learntechlib.org/p/33419/ Lowerison, G., Sclater, J., Schmid, R. F., & Abrami, P. C. (2006). Student perceived effectiveness of computer technology use in post-secondary classrooms. Computers & Education, 47(4), 465-489.  doi:10.1016/j.compedu.2004.10.014  Retrieved from https://pdfs.semanticscholar.org/fc9c/13f0187d3967217aa82cc96c188427e29ec9.pdf Martins, L. L., & Kellermanns, F. W. (2004). A model of business school students' acceptance of a web-based course management system. Academy of Management Learning & Education, 3(1), 7-26.  doi: 10.5465/AMLE.2004.12436815 Mayes, J. T. (2001). Quality in an e-University. Assessment & Evaluation in Higher Education, 26, 465-473.  doi:10.1080/02602930120082032 McCabe, S. (2007).  A brief history of the paralegal profession.  Michigan Bar Journal, 86(7), 18-21.  Retrieved from https://www.michbar.org/file/barjournal/article/documents/pdf4article1177.pdf McMillan, J. H. (2008). Educational Research: Fundamentals for the customer.  Boston, MA:  Pearson Education, Inc. Myers, C. B., Bennett, D., Brown, G., & Henderson, T. (2004). Emerging online learning environments and student learning: An analysis of faculty perceptions. Educational Technology & Society, 7(1), 78-86.  Retrieved from http://www.ifets.info/journals/7_1/9.pdf Myers, K. (2002). Distance education: A primer.  Journal of Paralegal Education & Practice, 18, 57-64. Nunnaly, J. (1978). Psychometric theory. New York: McGraw-Hill. Otter, R. R., Seipel, S., Graeff, T., Alexander, B., Boraiko, C., Gray, J., Petersen, K., & Sadler, K. (2013). Comparing student and faculty perceptions of online and traditional courses. The Internet and Higher Education, 19, 27-35.  doi:10.1016/j.iheduc.2013.08.001 Popham, W. J. (2000). Modern educational measurement: Practical guidelines for educational leaders. Boston, MA:  Allyn & Bacon. Rich, A. J., & Dereshiwsky, M. I. (2011). Assessing the comparative effectiveness of teaching undergraduate intermediate accounting in the online classroom format. Journal of College Teaching and Learning, 8(9), 19.  https://www.cluteinstitute.com/ojs/index.php/TLC/ Robinson, C., & Hullinger, H. (2008).  New benchmarks in higher education:  Student engagement in online learning.  The Journal of Education for Business, 84(2), 101-109.  Retrieved from http://anitacrawley.net/Resources/Articles/New%20Benchmarks%20in%20Higher%20Education.pdf Salkind, N. J. (2008). Statistics for people who think they hate statistics. Los Angeles, CA: Sage Publications. Santos, J. (1999, April). Cronbach's Alpha: A tool for assessing the reliability of scales.  Journal of Extension, 37, 2. Retrieved from https://www.joe.org/joe/1999april/tt3.php Seok, S., DaCosta, B., Kinsell, C., & Tung, C. K. (2010). Comparison of instructors' and students' perceptions of the effectiveness of online courses. Quarterly Review of Distance Education, 11(1), 25.  Retrieved from http://online.nuc.edu/ctl_en/wp-content/uploads/2015/08/Online-education-effectiviness.pdf Sheridan, K., & Kelly, M. A. (2010). The indicators of instructor presence that are important to students in online courses. Journal of Online Learning and Teaching, 6(4), 767-779.  Retrieved from http://jolt.merlot.org/vol6no4/sheridan_1210.pdf Shook, B. L., Greer, M. J., & Campbell, S. (2013). Student perceptions of online instruction. International Journal of Arts & Sciences, 6(4), 337.  Retrieved from https://s3.amazonaws.com/academia.edu.documents/34496977/Ophoff.pdf?AWSAccessKeyId=AKIAIWOWYYGZ2Y53UL3A&Expires=1508119686&Signature=J1lJ8VO0xardd%2FwH35pGj14UeBg%3D&response-content-disposition=inline%3B%20filename%3DStudent_Perceptions_of_Online_Learning.pdf Song, L., Singleton, E. S., Hill, J. R., & Koh, M. H. (2004). Improving online learning: Student perceptions of useful and challenging characteristics. The Internet and Higher Education, 7, 59-70.  doi:10.1016/j.iheduc.2003.11.003 Steiner, S. D., & Hyman, M. R. (2010). Improving the student experience: Allowing students enrolled in a required course to select online or face-to-face instruction. Marketing Education Review, 20, 29-34.  doi:10.2753/MER1052-8008200105 Stoel, L., & Hye Lee, K. (2003). Modeling the effect of experience on student acceptance of web-based courseware. Internet Research, 13(5), 364-374.  http://www.emeraldinsight.com/loi/intr Taggart, G., & Bodle, J. H. (2003). Example of assessment of student outcomes data from on-line paralegal courses: Lessons learned. Journal of Paralegal Education & Practice, 19, 29-36. Tanner, J. R., Noser, T. C., & Totaro, M. W. (2009). Business faculty and undergraduate students' perceptions of online learning: A comparative study. Journal of Information Systems Education, 20, 29-40.  http://jise.org/ Tung, C.K. (2007).  Perceptions of students and instructors of online and web-enhanced course effectiveness in community colleges (Doctoral dissertation). Retrieved from ProQuest Dissertations and Theses database (Publication No. AAT 3284232). Vodanovich, S. J.  & Piotrowski, C., & (2000). Are the reported barriers to Internet-based instruction warranted? A synthesis of recent research. Education, 121(1), 48-53.  http://www.projectinnovation.com/education.html Ward, M. E., Peters, G., & Shelley, K. (2010). Student and faculty perceptions of the quality of online learning experiences. The International Review of Research in Open and Distributed Learning, 11, 57-77.  Retrieved from http://www.irrodl.org/index.php/irrodl/article/view/867/1610? Wilkes, R. B., Simon, J. C., & Brooks, L. D. (2006). A comparison of faculty and undergraduate students' perceptions of online courses and degree programs. Journal of Information Systems Education, 17, 131-140. http://jise.org/